ANALISA PENERIMAAN PAJAK RESTORAN DI KANTOR BAPENDA KOTAWARINGIN TIMUR - Felin Tri Rahayu; Wahyudin Nor; Isnawati (Universitas Lambung Mangkurat, 2025)
ABSTRACT This research has the specific objective of understanding restaurant tax revenue in East Kotawaringin Regency during the Covid-19 pandemic and the concrete efforts implemented by Bapenda (Regional Revenue Agency), the Regional Revenue Agency, to maximize regional revenue targeting this sector. The COVID-19 pandemic, which was confirmed in early 2020, has had a number of significant impacts, particularly on the economy, including the restaurant sector, which is a major source of regional tax revenue. This study employed descriptive methods, with data collection techniques including observation, interviews, and documentation studies. The research findings confirm that restaurant tax revenue declined during the pandemic, but began to increase significantly in 2022 and 2023 in line with the recovery of economic activity and support from the government's National Economic Recovery (PEN) program. Bapenda East Kotawaringin has also taken strategic steps to support local economic recovery, particularly in the restaurant sector. In conclusion, collaboration between central government policies and regional implementation can encourage post-pandemic tax revenue recovery.